PENGARUH STORE ATMOSPHERE TERHADAP IMPULSE BUYING DENGAN SHOPPING EMOTION SEBAGAI VARIABEL MEDIASI - Wiranata, Axel; Suryadi, Nanang (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
The purpose of this research is to analyze the effect of store atmosphere on impulse buying with the mediation of shopping emotion. The population are visitors of minimarkets in Malang city, and the number of samples were calculated using the formula of Riduwan and Akdon, which is used to calculate the sample from an unknown number of populations. This study is categorized as explanatory research because it explains the position of variables being studied and the relationships between them. The data of this research was harvested from questionnaires distributed online to 97 respondents, who were selected using non-probability sampling method and purposive sampling technique with the criteria of people with the minimum age of seventeen years who have visited or made purchases in minimarkets in Malang city. The results of the Partial Least Squares analysis performed in SmartPLS 3.0 have led to findings that store atmosphere positively influences shopping emotion, that shopping emotion positively affects impulse buying, that store atmosphere does not positively influence impulse buying, and that shopping emotion mediates the effect of store atmosphere on impulse buying.